Praktiske tekster: – dokumentanalyse i studiet af pædagogisk praksis - Padovan-Özdemir, Marta (Tidsskrift for Professionsstudier, 2020)
Education is abundant in practical texts regulating, reflecting, guiding, and documenting. Nevertheless, practical texts often pass unnoticed in educational studies. This article discusses how poststructural documentary analysis can use practical texts for problematizing naturalized problematizations in education. Hence, the article takes educational problematizations of immigrant pupils as an example and objectifies it as a social question shaped by and shaping education. Then, key characteristics of practical texts, and how a text corpus can be established, is developed. In conclusion, the article advances a non-evaluative critique of education deploying systematic yet insubordinate analytical experimentation through aesthetic-effective montaging and (re)problematizations.